How adaptogens influence cognitive-mental performance: an integrative review (Research, Society and Development, 2022)
Given the high demand for optimizing personal performance in various aspects of social life, and in view of the prevalent stress situations in modern life, adaptogens, a term coined in 1943 by the Russians, were perfected. The aim of this study is to analyze these “toning” substances that increased physical performance in soldiers during World War II, and which acquired a new approach in the following years, taking a significant role in improving cognitive-mental performance. To this end, the study, an integrative literature review, will be based on the scientific platforms Scientific Electronic Library Online - SCIELO, Google Scholar, the U.S. National Library of Medicine (NLM) - PubMed and ScienceDirect. It is expected to find a correlation between the use of adaptogens in improving the response to stressful events, ultimately promoting cognitive-mental performance. Studies show that adaptogens have positive actions on memory, cognitive function and neuroprotection; also demonstrate anxiolytic, nootropic and anti-stress effect. Among the diseases, there is evidence that adaptogens may have benefit in Parkinson's and Alzheimer's disease. Ashwagandha, especially, is highlighted in studies. A limitation of the present work is that most recent studies obtained as results were also presented in the form of a literature review, making it clear that there is a need for new scientific evidence. Even so, the results support new research related to the understanding of the therapeutic properties of adaptogens, focusing mainly on clinical studies.